ANALISIS PENERAPAN SISTEM SMARTSHEET TERHADAP PENGENDALIAN PERSEDIAAN DI PT ABC: PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Rahmawati, Tia; Afif, M. Nur; Jamaludin Azis, Ayi (Politeknik Negeri Ambon, 2025)
Introduction: In the digital era, the success of information system implementation is highly influenced by user acceptance and behaviour. This study aims to analyse the influence of perceived ease of use, perceived usefulness, and attitude toward system use on inventory control, both directly and indirectly through the intention to use the system as a mediating variable, using the Technology Acceptance Model (TAM) approach.Methods: This research employed a quantitative method, utilising path analysis with SmartPLS. The sample consisted of 50 respondents who are users of the inventory control system at PT ABC.Results: The results showed that only attitude toward system use had a direct, positive, and significant effect on inventory control. Meanwhile, perceived ease of use and perceived usefulness did not show significant effects, either directly or through the mediation of the intention to use the system.Conclusion and suggestion: These findings highlight that attitude plays a dominant role in the successful implementation of the system in inventory control, whereas perceived ease of use and usefulness need to be supported by other factors such as training, organisational culture, and management support. Keywords: Technology Acceptance Model (TAM), Inventory Control, Interest in System Use.